Utility of the Posterior to Anterior Mitral Valve Leaflets Length Ratio in Prediction of Outcome of Percutaneous Balloon Mitral Valvuloplasty - Mahfouz, Ragab A. (Echocardiography (Mount Kisco, N.Y.), 2011)
Background: Scoring of mitral stenosis (MS) severity is very important for selection of patients for balloon mitral valvuloplasty (BMV). Objective: We propose a novel yet simple, independent parameter of MS severity based on the posterior mitral valve leaflet to anterior mitral valve leaflet length ratio (PMVL/AMVL length ratio). It could be a useful predictor to outcome of BMV. Subjects and methods: A total of 106 patients (mean age 29.1 ± 8.6 years) had MS with mitral valve score of eight or less. The length of anterior mitral valve leaflet and posterior mitral valve leaflet were measured. Patients were classified into group with ratio ≥1/2 and group of ratio <1/2. Eighty‐five healthy control subjects were studied. Results: Patients with PMVL/AMVL ratio ≥1/2 post‐BMV had lower transmitral gradients (4.5 ± 3.1 mmHg vs. 9.7 ± 2.1 mmHg, P < 0.002) and greater mitral valve area (MVA) (2.09 ± 0.3 cm2 vs. 1.5 ± 0.2 cm2, P < 0.001), lower pulmonary artery systolic pressure (PASP) (23.8 ± 14.3 mmHg vs. 34.2 ± 12.5 mmHg, P < 0.001), left atrial pressure (10.2 ± 6.7 mmHg vs. 18.9 ± 6.4 mmHg, P < 0.001), and lower incidence of de novo or worsening of mild mitral regurgitation (MR; 1.64% vs. 8.9%, 0% vs. 6.6%, P < 0.001). PMVL/AMVL length ratio was positively correlated with post‐BMV MVA (r = 0.69, P < 0.002), PASP (r = 0.592, P < 0.003), and negatively correlated with incidence of de novo or worsening of mild MR (r =–0.78, –0.93, P < 0.001). The regression analyses revealed that PMVL/AMVL ratio is the best and a reliable predictor of success and outcome of BMV, hazard ratio (95% confidence interval) 0.12 (0.05–52), P < 0.001. Conclusion: Length ratio of PMVL/AMVL assessment with echocardiography is an excellent simple predictor of post‐BMV mitral valve area and the cardiac events. (Echocardiography 2011;28:1068‐1073)